Voclosporin: a novel calcineurin inhibitor for the treatment of lupus nephritis. - Van Gelder, Teun; Lerma, Edgar; Engelke, Kory; Huizinga, Robert B. (Expert Review of Clinical Pharmacology, 2022)
INTRODUCTION: Lupus nephritis (LN) is a severe manifestation of systemic lupus erythematosus. Standard-of-care immunosuppressive therapies achieve poor complete renal response (CRR) rates, with considerable toxicity. This article reviews voclosporin, a novel oral calcineurin inhibitor (CNI) approved for treatment in adults with active LN by the US Food and Drug Administration (the FDA) in January 2021. AREAS COVERED: This review summarizes the chemical properties, pharmacokinetics, and pharmacodynamics of voclosporin, and its efficacy and safety in LN, based on literature review covering PubMed searches, manufacturers' websites, and documents produced by the FDA. EXPERT OPINION: Voclosporin is a CNI with a consistent pharmacokinetic-pharmacodynamic relationship resulting from enhanced calcineurin binding and reduced drug and metabolite load. This profile permits therapeutic efficacy in LN at a dose associated with relatively low calcineurin inhibition, and therefore a potentially improved safety profile. Pivotal trials demonstrated a significant benefit of adding voclosporin to standard therapy, with rapid reduction in proteinuria, and a clinically meaningful and significantly higher CRR rate at 1 year. At approved doses for LN, potential advantages of voclosporin versus historical experience with CNIs include lack of need for therapeutic drug monitoring, benign metabolic, lipid and electrolyte profile, and no impact on mycophenolate mofetil levels.
EVALuna2:520479